1965
DOI: 10.1021/ac60228a035
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Adsorbed Ethylene and Propylene Oxides by Distillation and Titration.

Abstract: the solution being titrated is made 12M in chloride ion, the decomposition rate is diminished to 0.3% per minute, but almost no chlorination of benzamide was noticed after 30 minutes. Bromine was also substituted for chlorine, but no ,IT-bromination was noticed in a reasonable time period.The following technique was then developed to eliminate errors due to the slight instability of the chlorinating agent. A direct titration was carried out, but the first experimental point after the end point was taken with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1968
1968
1972
1972

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Several analytical methods have been reported in the literature for the determination of ethylene oxide (25)(26)(27)(28)(29)(30)(31)(32)(33), ethylene glycol (27,34), and ethylene chlorohydrin (35)(36)(37)(38)(39). However, the present analytical requirements with respect to sensitivity, specificity, and time of analysis for the quantitative determination of ethylene oxide, ethylene chlorohydrin, and ethylene glycol in water-absorbable fabrics did not readily adapt to these methods.…”
mentioning
confidence: 99%
“…Several analytical methods have been reported in the literature for the determination of ethylene oxide (25)(26)(27)(28)(29)(30)(31)(32)(33), ethylene glycol (27,34), and ethylene chlorohydrin (35)(36)(37)(38)(39). However, the present analytical requirements with respect to sensitivity, specificity, and time of analysis for the quantitative determination of ethylene oxide, ethylene chlorohydrin, and ethylene glycol in water-absorbable fabrics did not readily adapt to these methods.…”
mentioning
confidence: 99%
“…Numerous researchers have reported on various aspects of ethylene oxide sterilization. Until 1965, the only residues found from the use of this epoxide were ethylene oxide per se, ethylene glycol, and diethylene glycol (1)(2)(3)(4)(5)(6)(7)(8). Wesley et al (9) showed that chlorohydrins could be formed in foods fumigated with ethylene oxide or propylene oxide in the presence of inorganic chloride, Methods for analyzing ethylene oxide-sterilized foods, plastic, and rubber materials for residual ethylene chlorohydrin (Zchloroethanol) were reported by various researchers (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…The introduction of gas sterilization of plastics has raised questions as to the possible entrapment of ethylene oxide in a plastic, which may cause a toxic effect when placed in contact with living tissues, and the effect sorbed ethylene oxide will have on possible changes in the physical-chemical properties of the medical plastic. It has been demonstrated (5) that higher concentrations of the epoxide can be taken up by polyethylene, gum rubber, and plasticized polyvinyl chloride (PVC) which reemphasizes the problem of gas entrapment in plastics. Hirose et al (2) and Clarke et al (3) have found that plastic tubings which have been ethylene oxide sterilized can cause significant hemolysis when placed in contact with human blood.…”
mentioning
confidence: 99%
“…The samples were analyzed by a procedure previously described by Gunther (5). Prior to milling each film, the rollers were carefully cleaned with practical grade stearic acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation